Adaptive Immunity in Pulmonary Sarcoidosis and Chronic Beryllium Disease - Greaves, Sarah A.; Atif, Shaikh M.; Fontenot, Andrew P. (Frontiers in Immunology, 2020)
Pulmonary sarcoidosis and chronic beryllium disease (CBD) are inflammatory granulomatous lung diseases defined by the presence of non-caseating granulomas in the lung. CBD results from beryllium exposure in the workplace, while the cause of sarcoidosis remains unknown. CBD and sarcoidosis are both immune-mediated diseases that involve Th1-polarized inflammation in the lung. Beryllium exposure induces trafficking of dendritic cells to the lung in a mechanism dependent on MyD88 and IL-1α. B cells are also recruited to the lung in a MyD88 dependent manner after beryllium exposure in order to protect the lung from beryllium-induced injury. Similar to most immune-mediated diseases, disease susceptibility in CBD and sarcoidosis is driven by the expression of certain MHCII molecules, primarily HLA-DPB1 in CBD and several HLA-DRB1 alleles in sarcoidosis. One of the defining features of both CBD and sarcoidosis is an infiltration of activated CD4+ T cells in the lung. CD4+ T cells in the bronchoalveolar lavage (BAL) of CBD and sarcoidosis patients are highly Th1 polarized, and there is a significant increase in inflammatory Th1 cytokines present in the BAL fluid. In sarcoidosis, there is also a significant population of Th17 cells in the lungs that is not present in CBD. Due to persistent antigen exposure and chronic inflammation in the lung, these activated CD4+ T cells often display either an exhausted or anergic phenotype. Evidence suggests that these T cells are responding to common antigens in the lung. In CBD there is an expansion of beryllium-responsive TRBV5.1+ TCRs expressed on pathogenic CD4+ T cells derived from the BAL of CBD patients that react with endogenous human peptides derived from the plexin A protein. In an acute form of sarcoidosis, there are expansions of specific TRAV12-1/TRBV2 T cell receptors expressed on BAL CD4+ T cells, indicating that these T cells are trafficking to and expanding in the lung in response to common antigens. The specificity of these pathogenic CD4+T cells in sarcoidosis are currently unknown.